The barker twins: boss for a day - De Paola, Tomie (Puffin Young Readers New York, 2012)
Moffie is ten minutes older than her twin brother, Morgie, and so she is always in charge, but when their mother says she is too bossy, Moffie decides to make Morgie boss for a day